Rhythmic Effect of Low Temperatures on Peculiarities of Free Radical Oxidation of Tissues of Brain Structures - Kotsar, V. L.; Babiychuk, V. G. (Problems of Cryobiology and Cryomedicine, 2008)
After application of rhythmic cold effect (RCE) there were studied the parameters of chemiluminescence and pro-oxidantantioxidant balance in the tissues of rat’s brain. There was noted more manifested change of the parameters in hypothalamus, direct dependences between total light sum S, TBA-active products, induced by lipid peroxidation and the inverse dependence of these parameters and GSH were found.